1999
DOI: 10.1080/014311699213569
|View full text |Cite
|
Sign up to set email alerts
|

Technical note and cover Fishing fleet lights and sea surface temperature distribution observed by DMSP/OLS sensor

Abstract: A night-time OLS (Operational Linescan System) visible± near-infrared (VNIR) channel image of the DMSP (Defense Meteorological Satellite Program) was overlaid on the simultaneously corrected OLS thermal infrared (TIR) channel image for the area around Japan. The OLS composite image showed a clear relationship between the location of ® shing¯eet lights detected by the VNIR channel and the sea surface temperature (SST) distribution observed by the TIR channel. Many ® shing¯eets were located at the cold side of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 2 publications
0
21
0
Order By: Relevance
“…Cho et al (1999) and Kiyofuji et al (2001) determined that the bright areas in the OLS images, created by 2-level slicing, were caused by light produced by the fishing vessels. Rodhouse et al (2001) reported the frequency of light occurrences in cloud-free imagery, and associated these lights with fishing vessels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cho et al (1999) and Kiyofuji et al (2001) determined that the bright areas in the OLS images, created by 2-level slicing, were caused by light produced by the fishing vessels. Rodhouse et al (2001) reported the frequency of light occurrences in cloud-free imagery, and associated these lights with fishing vessels.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of fishery oceanography, Cho et al (1999), Kiyofuji et al (2001), Rodhouse et al (2001) and Waluda et al (2002) examined nighttime visible images to determine the spatial distribution of fishing vessels. Cho et al (1999) and Kiyofuji et al (2001) determined that the bright areas in the OLS images, created by 2-level slicing, were caused by light produced by the fishing vessels.…”
Section: Introductionmentioning
confidence: 99%
“…Linescan System (OLS) sensor can effectively detects light emissions from squid vessels (Elvidge et al, 1999;Cho et al, 1999;Kiyofuji et al, 2001;Kim, 2002). Previous studies on the temporal analysis of fishing conditions for common squid were mostly based on long-term oceanic conditions and catch data and those on the spatial distributions of the fishing grounds for common squid focused on monthly variabilities of the fishing grounds (Kiyofuji et al, 2001;Kim, 2002;Cho et al, 2004;Choi et al, 2008 …”
Section: Meteorological Satellite Program (Dmsp) Operationalmentioning
confidence: 99%
“…Several different datasets, ranging from daily raw data to time-series "stable light" data, have been developed and applied to various observation areas. Popular applications of the DMSP/OLS nighttime images include monitoring human settlement [4,5]; estimating urban population [6] and population density [7], socio-economic activity [8], energy and electricity consumption [9], and gas emissions [10]; measuring impacts of urban growth on the environment [11]; detecting nocturnal fishing vessels [12]; mapping nighttime sky brightness [13] and forest fires [14]; assessing effects of emissions on ecosystem and human health [15,16]; and evaluating damage from natural disasters [17] and military action during wars [18].…”
Section: Introductionmentioning
confidence: 99%